2012
DOI: 10.3390/md10010163
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin Concentrations in Pleurobranchaea maculata: Temporal, Spatial and Individual Variability from New Zealand Populations

Abstract: Tetrodotoxin (TTX) is a potent neurotoxin that has been identified in a range of phylogenetically unrelated marine and terrestrial organisms. Tetrodotoxin was recently detected in New Zealand in Pleurobranchaea maculata (the grey side-gilled sea slug). From June 2010 to June 2011 wild specimens were collected from 10 locations around New Zealand. At one site (Narrow Neck Beach, Auckland) up to 10 individuals were collected monthly for 6 months. Attempts were also made to rear P. maculata in captivity. Tetrodot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…The fatal dose of tetrodotoxin to humans (50 kg body weight) is only 1–2 mg [4]. TTX has been detected from taxonomically diverse organisms across 14 different phyla, including pufferfish and amphibians [5,6], fish [7], cephalopods [8], gastropods [9,10,11], bivalves [12], crustaceans [13], starfishes [14,15], flatworms [16,17,18,19] and ribbonworms [17]. Several of the species that carry TTX have been found to be prey organisms of pufferfish [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatal dose of tetrodotoxin to humans (50 kg body weight) is only 1–2 mg [4]. TTX has been detected from taxonomically diverse organisms across 14 different phyla, including pufferfish and amphibians [5,6], fish [7], cephalopods [8], gastropods [9,10,11], bivalves [12], crustaceans [13], starfishes [14,15], flatworms [16,17,18,19] and ribbonworms [17]. Several of the species that carry TTX have been found to be prey organisms of pufferfish [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flatworms have been reported to contribute to the accumulation of toxins in other animals: dog neurotoxicosis has been shown to result from the consumption of the side-gilled sea slug ( Pleurobranchaea maculate ) in coastal areas of New Zealand [10], and subsequent investigation revealed that the sea slugs contained the toxin as a consequence of their predation of the polyclad flatworm Stylochoplana sp. [11]. Marine polyclad flatworms are common in coastal and rocky reefs worldwide [30], and they play influential roles in marine ecosystems [31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Captivity of the P. maculata specimen for 12 days prior to dissection and bacterial isolation may have influenced the microbiota present in our isolation process. Additionally, P. maculata have been shown to have high variability in TTX concentrations within individuals [32] suggesting an exogenous source of TTX. Whether this is due to environmental factors or variations in the abundance of bacterial producers is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…All are active hunters that prey on a wide variety of animals, though in some cases they have been described as having a preference for sea anemones (Ottaway 1977;Willan 1984;Cattaneo-Vietti et al 1993). Recently, high levels of tetrodotoxin (TTX) were found in adults, eggs and early larval stages of Pleurobranchaea maculata (McNabb et al 2010), though concentration varies greatly across individuals, seasons and populations (Wood et al 2012). TTX is an extremely potent neurotoxin that inhibits the propagation of action potentials in muscle and nerve cells; the ingestion of just 1-2 mg of TTX can cause death in adult humans (Noguchi & Arakawa 2008).…”
Section: Introductionmentioning
confidence: 99%